The Contestation of the Malay Arabic and Roman Literature: Shifts in Culture, Literature, and Religion - Dewi, Eva; Munthe, Bermawy; Arbi, Arbi; Afriza, Afriza (Arabiyatuna: Jurnal Bahasa Arab, 2023)
This study aimed to analyze and explicate the influence of the advent of Latin script (Roman script) on the progress of Malay-Arabic script culture, language, and religion in the archipelago. The arrival of Islam had a major influence on the language, religion, and culture of the archipelago through a script, known as the Malay Arabic script. In the archipelagic history, the reconstruction of local culture through an Arabic-Malay script has affected the growth and progress of civilization. The use of the Malay-Arabic script around the 13th century in the writing tradition in schools and Islamic boarding schools as a medium made it easier to read the Qur'an, to study Arabic grammar, and to learn various aspects of other scientific fields. After that, the situation changed due to the emergence of the Romance script in the 15th century, which was brought by Europeans to the Malay world or the Archipelago. Based on the type of qualitative research using a historical approach, it showed that there was a contestation of the Arabic-Malay script with the emergence of the Romance script in Indonesia. This could be seen from the following: 1) The position of the Arabic-Malay script, which had been popular in society and was entrenched in formal and normal institutions, had been increasingly lost due to the appearance of the Roman script. 2) It was difficult to find references related to religious, social, cultural, and political sciences written in the Arabic-Malay script. 3) The transition from using the Arabic-Malay script to the Roman script also had a religious mission, namely the eradication of Islamic symbols marked by many generations who did not understand the Arabic-Malay script as a medium to make it easier to read the Qur'an and understand religion. Based on this data, it is demonstrated that the study of Arabic-Malay script in today's society is decreasing, and the longer the majesty of the Arabic-Malay script as the Lingua Franca in archipelago civilization can be forgotten if it is not preserved and implemented in formal and non-formal education in Indonesia.